2018
DOI: 10.1002/ab.21761
|View full text |Cite
|
Sign up to set email alerts
|

Calming an aggressor through spontaneous post‐conflict triadic contacts: Appeasement in Macaca tonkeana

Abstract: Peaceful third-party interventions usually occur after an aggressive encounter and can be directed toward the victim or the aggressor. Macaca tonkeana, a cercopithecine species characterized by high levels of tolerance, frequently engage in consolatory contacts, which both calm the victim and reduce the probability of further attacks against him/her. Other post-conflict affiliative interventions such as reconciliation and quadratic affiliation are also common in this species. However, little attention has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…Moreover, on those occasions where individuals did groom, bout durations were somewhat shorter on conflict evenings compared to control evenings for grooming involving simulated aggressors (mean±SE duration, post-control: 34±11 s; post-conflict: 23±5 s; N=4 pairs of trials), while the reverse was true for grooming involving the matched dominant (post-control: 28±8 s; post-conflict: 34±8 s; N=4 pairs of trials); small sample sizes precluded statistical analysis. To our knowledge, this is the first evidence for a reduction in grooming of aggressors by bystanders; some previous studies have documented increased grooming of aggressors by bystanders in the immediate aftermath of a single contest (Cordoni and Palagi, 2015; Palagi et al, 2008; Pallante et al, 2018), whilst a few others have found no evidence for such an increase (Judge, 1991; Romero et al, 2008; Verbeek and de Waal, 1997). Subordinate bystanders could be avoiding the aggressor to reduce the likelihood of redirected aggression, which parallels the main strategy employed in the immediate aftermath of contests by meerkat ( Suricata suricatta ) and rook ( Corvus frugilegus ) victims attempting to avoid renewed aggression (Benkada et al, 2020; Kutsukake and Clutton-Brock, 2008).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Moreover, on those occasions where individuals did groom, bout durations were somewhat shorter on conflict evenings compared to control evenings for grooming involving simulated aggressors (mean±SE duration, post-control: 34±11 s; post-conflict: 23±5 s; N=4 pairs of trials), while the reverse was true for grooming involving the matched dominant (post-control: 28±8 s; post-conflict: 34±8 s; N=4 pairs of trials); small sample sizes precluded statistical analysis. To our knowledge, this is the first evidence for a reduction in grooming of aggressors by bystanders; some previous studies have documented increased grooming of aggressors by bystanders in the immediate aftermath of a single contest (Cordoni and Palagi, 2015; Palagi et al, 2008; Pallante et al, 2018), whilst a few others have found no evidence for such an increase (Judge, 1991; Romero et al, 2008; Verbeek and de Waal, 1997). Subordinate bystanders could be avoiding the aggressor to reduce the likelihood of redirected aggression, which parallels the main strategy employed in the immediate aftermath of contests by meerkat ( Suricata suricatta ) and rook ( Corvus frugilegus ) victims attempting to avoid renewed aggression (Benkada et al, 2020; Kutsukake and Clutton-Brock, 2008).…”
Section: Resultsmentioning
confidence: 56%
“…More recently, attention has shifted to the involvement of bystanders (contest nonparticipants) in post-conflict behaviour, particularly bystander-initiated affiliation with the victim as a means of avoiding redirected aggression (self-protection) or of providing substitute reconciliation or consolation (Fraser et al, 2009, 2008; Schino and Marini, 2012; Wittig and Boesch, 2010). There is also some evidence of bystander-initiated affiliation with the aggressor, which could function as appeasement to reduce the likelihood of redirected aggression (Cordoni and Palagi, 2015; Palagi et al, 2008; Pallante et al, 2018), and group-wide post-conflict affiliation among bystanders, perhaps to reduce conflict-induced anxiety (De Marco et al, 2010; Judge and Mullen, 2005). However, to the best of our knowledge, this research has focussed solely on interactions that occur in the immediate aftermath (usually within 10 minutes) of an aggressive contest; the possibility of delayed post-conflict management behaviour has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…the subjects was presumably still high (Macaca tonkeana, Palagi et al, 2014;Pallante et al, 2018). Following, from the 2nd to the 3rd minute after the conflict, the frequency of Y3 returned to baseline levels.…”
Section: Bystanders Y2 Bystanders Y3mentioning
confidence: 95%
“…which has been demonstrated to increase in the post-conflict in primate species (Eulemur fulvus, Palagi & Norscia, 2011; Papio hamadryas, Judge & Mullen, 2005; Macaca tonkeana,Palagi et al, 2014;Pallante et al, 2018; …”
mentioning
confidence: 99%
“…According to this hypothesis, former opponents may exchange a nonreproductive mount in the first minutes after a conflict, as a form of reconciliation. Postconflict nonreproductive mounts may help to reduce the probability of further aggression between former opponents, restore their social relationship, and facilitate other forms of postconflict affiliation, such as grooming (e.g., Aureli et al 1989;Aureli and van Schaik 1991;Aureli et al 2002;McFarland and Majolo 2013;Pallante et al 2018). Moreover, the short-term increase in anxiety that former opponents experience during or after a conflict, as measured by the frequency of self-directed behaviors such as selfscratching, quickly returns to baseline levels if former opponents exchange a nonreproductive mount (e.g., Aureli et al 1989Aureli et al 2002Castles et al 1996;Cooper et al 2007;Cords 1992;Hanby 1974;Kano 1980;Majolo et al 2005;Matsumura 1996;MacFarlane et al 2010).…”
Section: Introductionmentioning
confidence: 99%